Pengaruh Dukungan Organisasi, Kematangan Emosi dan Motivasi Kerja terhadap Komitmen Afektif Karyawan pada Dinas Pemadam Kebakaran dDan Penyelamatan Kota Yogyakarta - Yulita Tagumara; Prayekti Prayekti; Kusuma Chandra Kirana (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the effect of organizational support, emotional maturity and work motivation on the affective commitment of employees at the fire and rescue service in the city of Yogyakarta. This study uses a quantitative approach method. The population in the study amounted to 103 employees. Sampling by Accidental Sampling. Data were analyzed using Multiple Linear Regression equipped with the classical assumption test, T test and F test. The results showed that the Organizational Support variable had a positive and significant effect on Affective Commitment (Y), as evidenced by the results of the t test, which obtained a t count value of 2.263 > t table 1.675 and significant 0.028 <0.05. Then the variable Emotional Maturity (X2) has no significant effect on Affective Commitment (Y), as evidenced by the results of the t test, namely the t count value is 0.734 < t table 1.675 and is significant 0.467 > 0.05. And the variable Work Motivation (X3) has a positive and significant effect on the Affective Commitment variable (Y), evidenced by the results of the t test obtained t count 2.320 > t table 1.675 and significantly 0.025 <0.05. And simultaneously Organizational Support, Emotional Maturity and Work Motivation have a significant effect on Affective Commitment with α = 0.05. Keywords: Affective Commitment, Organizational Support, Emotional Maturity, Work Motivation